Persepsi Siswa Terhadap Pelaksanaan Layanan Bimbingan Dan Konseling Di SMP Negeri 2 Prabumulih - Nisrina Nahda, Novyela; Minarsi (At-Taujih : Bimbingan dan Konseling Islam, 2026)
Abstract: This study is motivated by the importance of understanding students’ perceptions of the implementation of guidance and counseling services in schools as part of supporting their development. Students’ perception is a crucial aspect because it can influence their attitudes and engagement in utilizing these services. This research aims to describe students’ perceptions of the implementation of guidance and counseling services in terms of cognitive, affective, and conative aspects. The study employed a quantitative approach with a descriptive method. Data were collected through a Likert-scale questionnaire administered to 192 students and analyzed using descriptive statistics, including mean, standard deviation, and percentage. The results indicate that students’ perceptions generally fall into the moderate category, with the dominance of moderate levels across all examined aspects. This finding suggests that students have a fairly good level of understanding, attitude, and behavioral tendency toward guidance and counseling services, although not yet optimal. Therefore, while the implementation of guidance and counseling services in schools has been carried out, further improvement is still needed to provide more optimal experiences for students. Keywords:  Students Perception; counseling services; cognitive aspect; affective aspect; conative aspect